0364 Cancer incidence and mortality in an Australian cohort of lead workers with historically collected blood lead data. (23rd June 2014) - Sim, Malcolm; MacFarlane, Ewan; Gwini, Stella; Del Monaco, Anthony; McLean, David; Pisaniello, Dino; Benke, Geza
Abstract : Objectives: To measure cancer incidence and mortality in a retrospective cohort of Australian lead-exposed workers. Method: The cohort comprised male lead workers who had been participants in state government occupational blood lead surveillance programs conducted since the 1970s. Historically collected blood lead level data were accessed from surveillance records. Linkage was undertaken to the National Death Index and the Australian Cancer Database to identify causes of death and incident cancers. Results: 4114 male subjects were followed for an average of 16.2 years, giving 68 172 person years. All incident cancers were lower than expected (SIR 83, 95% CI: 73–95). The incidence of liver cancer was elevated (SIR 217, 95% CI 103–454), as was the incidence of oesophageal cancer (SIR 240, 95% CI: 129–447). Among those cohort members with at least one blood lead result in excess of 30µg/dL, oesophageal cancer incidence was elevated (SIR 755; 95% CI 314–1813). Other cancer types were not found to occur in excess. All cause mortality was greater than expected (SMR 111; 95% CI 101–123) based on 406 deaths. Non-malignant digestive system deaths (SMR 167; 95% CI 110–250) and deaths from external causes (SMR 135; 95% CI 105–174) were also elevated. Conclusions: The increase in gastrointestinal stract cancers is consistent with some previous studies of lead workers. Confounding from liefestyle factors, such as alcohol, could not be examined. It is planned to include this cohort in an international pooling study of lead exposed workers.